(untitled) (Studia theodisca, 2017)
The main focus of this essay is the discursive analysis of “Reich” as an article of faith in the poetry volume Die Fanfare. Gedichte der deutschen Erhebung by Heinrich Anacker (1901-1971). Looking back to the original theological foundation of the concept “Third Reich” in connection with the debate about whether National Socialism could be considered as a political religion, “Reich” is described as a possible article of faith of the Nazi creed. In Anacker’s National Socialist biased propaganda poetry, “Reich” appears, in fact, as a sacred and even as a quasi-religious entity.